Patterns of antidepressant use during pregnancy: a nationwide population‐based cohort study - Bénard‐Laribière, Anne (Br J Clin Pharmacol, 2018)
AIMS: We explored the patterns of antidepressant use during pregnancy. METHODS: A cohort of women who started a pregnancy in 2014 was identified using data from the French reimbursement healthcare system (covering approximately 99% of the population). Antidepressant usage (initiated before or during pregnancy) was assessed. Explored changes in antidepressant treatment were: associations, switches, discontinuation and resumption of antidepressants during pregnancy. RESULTS: The cohort included 766 508 pregnancies (755 519 women). Antidepressant use during pregnancy was 25.7 per 1000 [95% CI: 25.3–26.0]. New use concerned 3.9 per 1000 [95% CI: 3.7–4.0]; the most initiated class during pregnancy was selective serotonin reuptake inhibitors (SSRIs), while the most prescribed individual drug in second and third trimesters was amitriptyline, a tricyclic. Most changes were observed before pregnancy and during the first trimester: 63% of ongoing treatments in the year before pregnancy were discontinued before conception; 68% of treatments maintained after conception were discontinued during the first trimester; switches or antidepressant associations mostly occurred during the periconceptional period or during the first trimester. Regardless of initial antidepressant, switches to sertraline were the most frequent. Associations mainly consisted of a prescription of tri‐/tetracyclic or mirtazapine/mianserin in addition to an SSRI. Discontinuation during pregnancy led to treatment resumption in 22% of pregnancies. CONCLUSIONS: These results suggest that pregnancy was planned or the treatment especially adapted in accordance with existing recommendations in a large proportion of women under antidepressants or in whom such treatments have been initiated after starting a pregnancy.